Biracial in America : forming and performing racial identity - Khanna, Nikki, 1974- (Lexington Books, 2011)
"Elected in 2008, Barack Obama made history as the first African American President of the United States. Though recognized as the son of his white Kansas-born mother and his Kenyan father, the media and public have nonetheless pigeonholed him as black, and he too self-identifies as such. Obama's experiences as a biracial American with black and white ancestry, although compelling because of his celebrity, however, is not unique and raises several questions about the growing number of black-white biracial Americans today: How are they perceived by others with regard to race? How do they tend to identify? And why? Taking a social psychological approach, this book identifies influencing factors and several underlying processes shaping racial identity. Unlikeprevious studies which examine racial identity as if it was a one-dimensional concept, this book examines two dimensions of identity - a public dimension (how they identify themselves to others) and an internalized dimension (how they see themselves internally) - noting that both types of identity may not mesh, and in fact, they may be quite different from one another. Moreover, this study investigates the ways in which biracial Americans perform race in their day-to-day lives. One's race isn't simply something that others prescribe onto the individual, but something that individuals 'do.' The strategies and motivations for performing black, white, and biracial identities are explored"--Provided by publisher.